The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/ird.2706
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensively evaluating and modelling droplet diameters and kinetic energies of low‐pressure sprinklers

Abstract: Proper droplet diameter and kinetic energy can effectively reduce the risk of soil erosion during low-pressure sprinkler irrigation. In this study, we comprehensively evaluated the radial distributions of droplet diameter, velocity, kinetic energy, kinetic energy per unit droplet volume, and specific power for three common low-pressure sprinklers, i.e. Nelson D3000, R3000 and Komet KPT, with two operating pressures (103 and 138 kPa) and three nozzle outlet diameters (3.97, 5.95 and 7.94 mm). Additionally, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 52 publications
3
6
0
Order By: Relevance
“…Similar outcomes in sprinkler irrigation experiments on flat land have been observed by other researchers [18,21,33]. This was expected because small diameter droplets predominate near the sprinkler [16,34,35]. Meanwhile, the specific surface area (surface area per unit volume) of the small droplet is large [36]; therefore, its air friction resistance ratio is relatively high, and the horizontal droplet velocity rapidly approaches zero [37].…”
Section: Radial Droplet Impact Angle Distribution On Sloping Landsupporting
confidence: 79%
See 2 more Smart Citations
“…Similar outcomes in sprinkler irrigation experiments on flat land have been observed by other researchers [18,21,33]. This was expected because small diameter droplets predominate near the sprinkler [16,34,35]. Meanwhile, the specific surface area (surface area per unit volume) of the small droplet is large [36]; therefore, its air friction resistance ratio is relatively high, and the horizontal droplet velocity rapidly approaches zero [37].…”
Section: Radial Droplet Impact Angle Distribution On Sloping Landsupporting
confidence: 79%
“…However, the sprinkler droplets that continue to hit the soil can easily cause soil surface sealing, resulting in surface runoff on sloping land and affecting the absorption of water by crops [9,10]. Results from previous studies have suggested that soil surface sealing is mainly due to the separation of soil particles from aggregates [11,12], and it is generally considered to be closely related to sprinkler droplet kinetic energy [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As one of the common high-efficiency water-saving irrigation devices in farmland, the center pivot irrigation system has rapidly applied in China in recent years due to its advantages including high irrigation efficiency, wide coverage of irrigated area, high automation, and low labor costs (Yan et al, 2020;Baiamonte et al, 2021;Hui et al, 2022a). By the end of 2019, there were more than 18×10 3 sets of center pivot and linear-move irrigation systems used in China, with an irrigation area of nearly 6×10 5 hm 2 , which accounted for about 14.2% of the total sprinkler irrigation area (Hui et al, 2022b). With the global objective of peaking the carbon emissions and carbon neutrality, it is imperative to realize the low-pressure and energy-saving sprinkler irrigation.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the strong wind resistance characteristics of OSPS make it highly competitive in the sprinkler marketplace (Manke et al, 2019). Nowadays, numerous studies have focused on the water application rate, droplet diameter, kinetic energy, and other indicators of low-pressure sprinklers (Yan et al, 2010;Sayyadi et al, 2014;Robles et al, 2019;Hui et al, 2022b). However, the impact angle and shear stress of the droplet have rarely been investigated, which is not conducive to further revealing the soil erosion mechanism under low-pressure sprinkler irrigation.…”
Section: Introductionmentioning
confidence: 99%